Paranormal activity [videorecording (DVD)] - Peli, Oren; Peli, Oren; Peli, Oren; Featherston, Katie; Sloat, Micah; Fredrichs, Mark; Palmer, Ashley; Armstrong, Amber (DreamWorks Pictures, 2009)
Katie and Micah are a young middle class couple who are engaged to be married. After moving into a suburban 'starter' house in San Diego, California, they begin hearing noises while trying to sleep. Not knowing if the presence is demonic or not, they attempt communicating through a Ouija board, angering the spirit further. Now they may never sleep again, or they may never wake up!